Fungal corneal ulcers of onion harvesters in southern Taiwan. Issue 6 (1st June 1999) - Lin, S H; Lin, C P; Wang, H Z; Tsai, R K; Ho, C K
Abstract : Fungal corneal ulcers related to agriculture has been reported throughout the world, especially in tropical areas. Most of them were sporadic and had histories of ocular trauma or use of topical corticosteroids and topical antibiotics. Five onion harvesters had fungal corneal ulcers during the same harvest period in Southern Taiwan. The authors think that this is the first report of a group occurrence relating to agricultural workers. Although all of the patients improved after medical and surgical management, their vision was greatly decreased. It is suggested that the tropical climate, the harvest procedure, the characteristic monsoon, and lack of eye protection were involved. Therefore, the importance of the eye protection, hygiene education, and improving medical care to reduce the occurrence of fungal corneal ulcer in agriculture workers must be emphasised.